ANALISIS KUALITAS PRODUK, CITRA MEREK DAN PERSEPSI HARGA TERHADAP LOYALITAS PELANGGAN YANG DIMEDIASI OLEH KEPUASAN PELANGGAN (Studi Pada Pelanggan Nissan Di Kota Semarang Tahun 2017) - Charis Masruchin, 12.05.51.0078; Marlien, RA (Students' Journal of Economic and Management, 2017)
Customer satisfaction is one of the company's factors to gain high loyalty from its customers. Customer satisfaction has direct relevance to product quality, brand image and price perception. Customers whose expectations are met or even exceeded will spread positive news regarding the perceived performance to others. By being a satisfied customer, the value of customer interest in the products and services offered by Nissan will also increase. This is certainly very beneficial to the Nissan as a manufacturer, because customers will remain faithful to all forms of services provided by the Nissan car manufacturer. This study aims to analyze product quality, brand image and price perceptions of customer loyalty mediated by customer satisfaction Nissan in Semarang City in 2017. This research is a descriptive research. The number of samples is 100 respondents. The research instrument used questionnaire. Data analysis using multiple linear regression and path analysis. The results showed that product quality positively affects customer loyalty mediated by customer satisfaction. Brand image positively affects customer loyalty mediated by customer satisfaction. Price perceptions have a positive effect on customer loyalty mediated by customer satisfaction. Keywords: product quality, brand image, price perception, customer satisfaction, customer loyalty.